Examining the role of monetary aggregates in China - José R. Sánchez-Fung (Bank of Finland, Institute for Economies in Transition (BOFIT), 2012)
The paper examines the relative significance of monetary aggregates and interest rates in China using the information approach to monetary policy. The analysis reveals the superiority and robustness of a narrow monetary aggregate in contributing information about future movements in inflation.
URN:NBN:fi:bof-201408072027
Keywords: E52; 330; monetary policy and inflation; information approach; monetary aggregates; interest rates; China